THE INFLUENCE OF THIN CAPITALIZATION, LIQUIDITY, PROFITABILITY, AND RELATED PARTY TRANSACTIONS ON TAX AGGRESSIVENESS IN INFRASTRUCTURE, UTILITIES, AND TRANSPORTATION COMPANIES IN THE 2021-2023 PERIOD - Umniyah Addin; Sarwenda Biduri (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: To examine how Thin Capitalization, Liquidity, Profitability, and Related Party Transactions influence Tax Aggressiveness in Infrastructure, Utilities, and Transportation companies listed on the IDX during 2021–2023. Method: A quantitative approach using secondary data. The population consists of 80 companies, with 48 selected through purposive sampling. Data were analyzed using multiple linear regression with SPSS version 27. Results: Thin Capitalization, Liquidity, Profitability, and Related Party Transactions each show a significant effect on Tax Aggressiveness. Novelty: This study provides integrated empirical evidence on four financial and transactional determinants of tax aggressiveness specifically within the Infrastructure, Utilities, and Transportation sector—an industry segment that has been rarely examined as a combined model in prior research.